# Chapter 4 - Section 4.2 - Exponential Functions - 4.2 Exercises - Page 409: 43

See the picture below.

#### Work Step by Step

The parent function is $f(x)=(\frac{1}{3})^x$ (with red) the given function is $g(x)=(\frac{1}{3})^{x+2}$ (with blue). The parent function can be graphed by calculating a few coordinates and connecting them with a smooth curve: $f(-2)=(\frac{1}{3})^{-2}=9$ $f(-1)=(\frac{1}{3})^{-1}=3$ $f(0)=(\frac{1}{3})^0=1$ $f(1)=(\frac{1}{3})^1=\frac{1}{3}$ $f(2)=(\frac{1}{3})^2=\frac{1}{9}$ For every corresponding x-value the following equation is true: $f(x+2)=g(x)$ This means that the graph is translated 2 units left ($g(x)$ involves a horizontal shift of 2 to the left). Because when f(x)=g(x), the g(x) function acts like the f(x). For example if $f(0)=1$ in the original $f(x)$, this will be equal to $g(-2)=f(-2+2)=f(0)=1$. $Here, f(0)=g(-2)$ also, $f(1)=g(-1)$ We can see that here, each point in the parent function was moved to the left by 2 units.

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.